An Intrinsically Magnetic Epicardial Patch for Rapid Vascular Reconstruction and Drug Delivery - Bei Qian; Ao Shen; Shixing Huang; Hongpeng Shi; Qiang Long; Yiming Zhong; Zhaoxi Qi; Xiaojun He; Yecen Zhang; Wangxi Hai; Xinming Wang; Yanna Cui; et al. (Advanced Science, 2023)
Abstract Myocardial infarction (MI) is a major cause of mortality worldwide. The major limitation of regenerative therapy for MI is poor cardiac retention of therapeutics, which results from an inefficient vascular network and poor targeting ability. In this study, a two‐layer intrinsically magnetic epicardial patch (MagPatch) prepared by 3D printing with biocompatible materials like poly (glycerol sebacate) (PGS) is designed, poly (ε‐caprolactone) (PCL), and NdFeB. The two‐layer structure ensured that the MagPatch multifariously utilized the magnetic force for rapid vascular reconstruction and targeted drug delivery. MagPatch accumulates superparamagnetic iron oxide (SPION)‐labelled endothelial cells, instantly forming a ready‐implanted organization, and rapidly reconstructs a vascular network anastomosed with the host. In addition, the prefabricated vascular network within the MagPatch allowed for the efficient accumulation of SPION‐labelled therapeutics, amplifying the therapeutic effects of cardiac repair. This study defined an extendable therapeutic platform for vascularization‐based targeted drug delivery that is expected to assist in the progress of regenerative therapies in clinical applications.